BANTUAN PEMBUATAN CHART OF ACCOUNT DAN PELATIHAN MENGENAI SOFTWARE AKUNTANSI BAGI KARYAWAN XP INDONESIA - Kristian, Michelle; Velisia, Stefani; Velinda (Jurnal Serina Abdimas, 2023)
ABSTRACT Chart of accounts is a list of all account codes that have been compiled in a coherent and orderly manner so that they can be sorted based on a combination of numbers and letters which allows the account to be placed into the General Ledger. Chart of Accounts is useful for making it easier for companies to record incoming or outgoing transactions, so that accounting reports can be displayed accurately. Financial reports are useful for assisting companies in the right decision making process. Because there have been several changes in the old accounting system used, which still uses Excel and the staff are busy with routine work and so far financial analysis is only based on mandatory ones which are carried out routinely, and also the accounting department is not accurate enough in providing information from financial reports. With the current conditions, assistance is needed to create a Chart of Accounts and Training on Accounting Software based on financial accounting standards in Indonesia (SAK ETAP) for XP Indonesia Employees. Accountant job requirements can increase computer-related skills, such as financial analysts, security data centres, management consultants, information systems, which are very much needed in various industrial sectors, so we must follow developments in information technology, computers and online media in the financial services industry. The aim of the PKM activity is to provide assistance in creating a Chart of Accounts and accounting software training based on the PSAK ETAP basis which will be explained by Untar FEB Team. The result of PKM activities is that employees can work effectively and the resulting financial reports are accurate and in accordance with the PSAK ETAP. ABSTRAK Chart of account merupakan daftar keseluruhan kode akun yang telah disusun secara runtut dan teratur sehingga dapat diurutkan berdasarkan paduan angka dan huruf yang memungkinkan akun tersebut dapat ditempatkan ke dalam General Ledger. Chart of Account berguna untuk mempermudah perusahaan dalam mencatat transaksi masuk atau keluar, sehingga laporan akuntansi dapat ditampilkan secara akurat. Laporan keuangan berguna untuk membantu perusahaan dalam proses pengambilan keputusan yang tepat. Karena terdapat beberapa perubahan dalam sistem akuntansi lama yang digunakan, dimana masih menggunakan excel dan terdapat kesibukan para staf dalam pekerjaan rutin dan selama ini analisis keuangan hanya berdasarkan mandatory yang dilakukan secara rutin, dan juga bagian akuntansi belum cukup akurat dalam memberikan informasi dari laporan keuangan. Dengan kondisi terkini, maka diperlukan bantuan Pembuatan Chart of Account dan Pelatihan mengenai Software Akuntansi berdasarkan standar akuntansi keuangan di Indonesia (SAK ETAP) bagi Karyawan XP Indonesia. Kebutuhan pekerjaan akuntan dapat meningkatkan keahlian terkait dengan komputer, seperti analis keuangan, pusat data keamanan, konsultan manajemen, sistem informasi, dimana sangat dibutuhkan di berbagai sektor industri, sehingga kita harus mengikuti perkembangan teknologi informasi, computer, dan media daring di industri jasa keuangan. Tujuan dari Kegiatan PKM adalah memberikan bantuan pembuatan Chart of Account dan pelatihan software accounting berdasarkan dengan basis PSAK ETAP yang akan dipaparkan oleh Tim FEB Untar. Hasil dari kegiatan PKM adalah agar Karyawan dapat bekerja secara efektif dan laporan keuangan yang dihasilkan menjadi akurat dan sesuai basis PSAK ETAP.